2019
DOI: 10.1002/cphc.201900601
|View full text |Cite
|
Sign up to set email alerts
|

Undesired Bulk Oxidation of LiMn2O4 Increases Overpotential of Electrocatalytic Water Oxidation in Lithium Hydroxide Electrolytes

Abstract: Chemical and structural changes preceding electrocatalysis obfuscate the nature of the active state of electrocatalysts for the oxygen evolution reaction (OER), which calls for model systems to gain systematic insight. We investigated the effect of bulk oxidation on the overpotential of ink‐casted LiMn2O4 electrodes by a rotating ring‐disk electrode (RRDE) setup and X‐ray absorption spectroscopy (XAS) at the K shell core level of manganese ions (Mn−K edge). The cyclic voltammogram of the RRDE disk shows pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 79 publications
1
48
0
6
Order By: Relevance
“…While many of the more active Mn-based electrocatalysts contain Mn 4+ in addition to Mn 3+ [10,39,40,[81][82][83][84], those with predominately Mn 4+ are inactive [3]. Recently, Baumung et al [18] showed that (bulk) oxidation of LiMn 3.5+ 2 O 4 toward Mn 4+ increases the overpotential of the OER. This can be rationalized qualitatively using the occupancy of the e g orbitals as proposed by Suntivich et al [47]where the lowest overpotential is predicted for an e g occupancy of about one (Mn 3+ ) and both higher or lower e g occupancy (i.e.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…While many of the more active Mn-based electrocatalysts contain Mn 4+ in addition to Mn 3+ [10,39,40,[81][82][83][84], those with predominately Mn 4+ are inactive [3]. Recently, Baumung et al [18] showed that (bulk) oxidation of LiMn 3.5+ 2 O 4 toward Mn 4+ increases the overpotential of the OER. This can be rationalized qualitatively using the occupancy of the e g orbitals as proposed by Suntivich et al [47]where the lowest overpotential is predicted for an e g occupancy of about one (Mn 3+ ) and both higher or lower e g occupancy (i.e.…”
Section: Samplementioning
confidence: 99%
“…Usually, degradation is associated with changes of the surface and bulk oxide composition, long range order (i.e. crystallinity) and/or microstructure, but it can be also caused by detachment, particle agglomeration, or blocking by oxygen bubbles [17][18][19][20][21]. These material modifications due to activation and degradation can be electrochemically observed as changes in overpotential at fixed current or changes in current at fixed overpotential [17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…LiMn 2 O 4 and its close derivatives, thus, became a mainstay in the early years of aqueous lithium‐ion battery research 31–37 . LiMn 2 O 4 would also become part of work developing supercapacitors due to its stability 38 and high rate capability 39 …”
Section: Aqueous Lithium‐ion Batteries: the Early Daysmentioning
confidence: 99%
“…For flow rates of 0.5 to 8 ml/min, the Reynolds number is calculated as Re DEFC = 2.5-40 ( = 0.01004 cm 2 /s at 20 °C) using Eq. (12). The low Reynolds number (˂˂2000) suggests that the cell has a laminar flow, which allows a controlled mass transport to and from the working electrodes.…”
Section: Construction Of the Defcmentioning
confidence: 99%
“…Generator-collector experiments are most commonly performed using rotating ring-disk electrodes (RRDE; Fig. 1a), [11][12][13] which are commercially available from several manufacturers. In this kind of setup, a rotated disk is the generator electrode.…”
Section: Introductionmentioning
confidence: 99%